Equity valuation: CTT - Correios de Portugal, S.A. - Brás, Ivo Gonçalo Ventura (2022)
Equity valuation has always been a subject of interest for companies, stakeholders and corporate finance specialists. The purpose of this Master in Finance project is to valuate CTT - Correios de Portugal, S.A. (from now on referred to as only CTT), a Portuguese company listed on Euronext Lisbon and one of the biggest in the country. Although its main operation, which largely consists of postal services, has been facing difficulties in the form of revenue and volume decreases, the innovation through e-commerce, investment in parcels and specially CTT Bank and financial services, have been propelling CTT to a stable growth, maintaining its importance in this sector of the Portuguese economy. As part of the valuation process, the end goal for this work is to assess if CTT’s shares were under or overvalued and, consequently, issue a recommendation on the action to take regarding them. To do this, the method chosen was the discounted cash flow model, namely the firm valuation approach (free cash flows to the firm), which is later complemented by another approach, relative valuation. The share price of CTT was subsequently computed and subject to a sensitivity analysis in order to better understand its possible variations. Through the application of the free cash flows to the firm methodology, CTT target price per share, as of 31st December 2020, was estimated to be of €4.25. Given that the share closed at €2.35 on 31st December 2020, it is concluded that it was undervalued, hence a buy recommendation is suggested.